The relationship between social support and Internet addiction among Chinese college freshmen: A mediated moderation model - Lu, Xiaoman; Zhang, Mengnan; Zhang, Jingqiu (Frontiers in Psychology, 2023)
Internet addiction has become a worldwide mental health problem, and this problem is particularly prominent in China. To find out the influencing factors and the mechanism of Internet addiction among college freshmen, and to form scientific prevention and intervention plan on this basis, this study adopts the cluster sampling method to select 322 college freshmen in a typical postsecondary school in Shandong Province to investigate the relationship between social support, network-related maladaptive cognition, gender, and the degree of Internet addiction. The findings of this study are as follows: (1) After controlling age and family location, social support had a significant negative predictive effect on Internet addiction; (2) Gender acted as a moderator between the relationship of social support and Internet addiction; (3) Additionally, the moderating effect of gender was completely mediated by network-related maladaptive cognition. In general, there is a mediated moderating effect between social support and Internet addiction. That is, gender plays a moderating role between social support and Internet addiction, and this moderating effect is mediated by network maladaptive cognition.